Intracellular codelivery of anti-inflammatory drug and anti-miR 155 to treat inflammatory disease - Chao Teng; Chenshi Lin; Feifei Huang; Xuyang Xing; Shenyu Chen; Ling Ye; Helena S. Azevedo; Chenjie Xu; Zhengfeng Wu; Zhongjian Chen; Wei He (Elsevier, 2020)
Atherosclerosis (AS) is a lipid-driven chronic inflammatory disease occurring at the arterial subendothelial space. Macrophages play a critical role in the initiation and development of AS. Herein, targeted codelivery of anti-miR 155 and anti-inflammatory baicalein is exploited to polarize macrophages toward M2 phenotype, inhibit inflammation and treat AS. The codelivery system consists of a carrier-free strategy (drug-delivering-drug, DDD), fabricated by loading anti-miR155 on baicalein nanocrystals, named as baicalein nanorods (BNRs), followed by sialic acid coating to target macrophages. The codelivery system, with a diameter of 150 nm, enables efficient intracellular delivery of anti-miR155 and polarizes M1 to M2, while markedly lowers the level of inflammatory factors in vitro and in vivo. In particular, intracellular fate assay reveals that the codelivery system allows for sustained drug release over time after internalization. Moreover, due to prolonged blood circulation and improved accumulation at the AS plaque, the codelivery system significantly alleviates AS in animal model by increasing the artery lumen diameter, reducing blood pressure, promoting M2 polarization, inhibiting secretion of inflammatory factors and decreasing blood lipids. Taken together, the codelivery could potentially be used to treat vascular inflammation.